New cladotherian mammal from southern Chile and the evolution of mesungulatid meridiolestidans at the dusk of the Mesozoic era - Agustín G. Martinelli (Nature Portfolio, 2021)
Abstract In the last decades, several discoveries have uncovered the complexity of mammalian evolution during the Mesozoic Era, including important Gondwanan lineages: the australosphenidans, gondwanatherians, and meridiolestidans (Dryolestoidea). Most often, their presence and diversity is documented by isolated teeth and jaws. Here, we describe a new meridiolestidan mammal, Orretherium tzen gen. et sp. nov., from the Late Cretaceous of southern Chile, based on a partial jaw with five cheek teeth in locis and an isolated upper premolar. Phylogenetic analysis places Orretherium as the earliest divergence within Mesungulatidae, before other forms such as the Late Cretaceous Mesungulatum and Coloniatherium, and the early Paleocene Peligrotherium. The in loco tooth sequence (last two premolars and three molars) is the first recovered for a Cretaceous taxon in this family and suggests that reconstructed tooth sequences for other Mesozoic mesungulatids may include more than one species. Tooth eruption and replacement show that molar eruption in mesungulatids is heterochronically delayed with regard to basal dryolestoids, with therian-like simultaneous eruption of the last premolar and last molar. Meridiolestidans seem endemic to Patagonia, but given their diversity and abundance, and the similarity of vertebrate faunas in other regions of Gondwana, they may yet be discovered in other continents.